Business Strategy and Environmental Performance - Juniarti Juniarti; Camelia Florensia Beoang; Meliani Fitri Salim Prayogo; Parulian Adinata Samosir (Jurnal Akuntansi dan Keuangan, 2021)
Business strategy choices are very influential in a company’s environmental performance. Companies that choose the cost leadership strategy tend to streamline their expenses which leads to them overlooking the environmental cost. Meanwhile, differentiation strategy encourages companies to accommodate environmental costs to fulfill customers’ demands. Therefore, this research aims to examine the impacts of the strategy choices on environmental performance, which has not been focused on by previous researchers. This research’s samples are public companies that are consistently participating in the PROPER program during the 2012-2017 period. 228 company years fulfill the sample criteria. The data are processed using the GRETL application that is fit for processing the panel data. We apply two proxies to measure each strategy choice. Cost leadership is proxied with EPAS and SPPE while differentiation is measured with SGAS and SCGS. This research’s findings are, firstly, companies that choose the cost leadership strategy have lower environmental performances, and, secondly, companies with differentiation strategy have high environmental performances. However, not all proxies used to measure the cost leadership and differentiation strategies support the impacts of strategy choices on environmental responsibilities performance.